Potensi Bunga Telang (Clitoria ternatea L.) terhadap Sindrom Metabolik - Rupadani, Ni Luh Desy; Ernawati, Desak Ketut; Trapika, I.G.M.G. Surya Candra (Jurnal Riset Hesti Medan, 2024)
Sedentary lifestyle such as consuming fast food, fatty foods, smoking and rarely doing physical activity are triggers for metabolic syndrome. Metabolic syndrome is a collection of risk factors for metabolic and cardiovascular disease consisting of dyslipidemia, obesity, hypertension and insulin resistance. The presence of metabolic syndrome will lead to a doubled risk of cardiovascular disease compared to patients without metabolic syndrome. Cardiovascular disease is the leading cause of death worldwide. One of the plants that has benefits for preventing and treating metabolic syndrome is telang (Clitoria ternatea L.). Almost all parts of the telang plant can be used for preventive and medicinal therapies, but the most commonly used part of the plant is the flower. Telang flowers are known to have antiobesity, antidiabetic, antioxidant and other activities. Telang flowers have chemical compound components in the form of flavonoids, alkaloids, tannins, saponins, phenolic acids and terpenoids.